The effect of envelope components on thermal performance of rural houses in Hubei, China. Issue 9 (November 2019) - Li, Kun; Zhao, Tian
Most farm houses in China are self-built. The process of design and construction of these houses generally lack theoretical and technical support logic and they do not comply with national standards. The objective of this research was to improve the thermal properties of farm houses in hot summer and cold winter regions of China. A rural house in Zijin Zhuang village, Hubei Province was selected to identify ways to improve its enclosure and the thermal performance of its building envelope. This paper considers the relationship between enclosure structure and thermal comfort, by quantitative comparison and analysis of thermal environmental data before and after refurbishment. DesignBuilder software was used to simulate the amount of energy consumed to attain the same indoor thermal comfort before and after the refurbishment. This study provides a reference exemplar for the construction of these farm houses in hot summer and cold winter areas.